META-ANALISIS : EFEK KUERSETIN SEBAGAI ANTIDIABETES DALAM MENURUNKAN KADAR GLUKOSA DARAH PADA STUDI TIKUS DIABETES MELITUS TIPE 2 - Mumtazya, Faiz Nabila; Fitria, Anisa Lailatul; Atmaka, Dominikus Raditya; Adi, Annis Catur (Darussalam Nutrition Journal, 2025)
Background: Diabetes Mellitus is a long-term condition that occurs when blood glucose levels increase because the body cannot use insulin effectively. Risk factors that cannot be changed include age, gender and heredity. Meanwhile, risk factors that can be changed include diet, daily habits such as rest, physical activity and stress management. Quercetin can reduce blood glucose levels so it can be used as an anti-diabetic alternative. Objective: this meta-analysis is to determine the effect of quercetin in reducing blood sugar levels in type 2 DM mice. Method: This research uses a meta-analysis method with experimental studies from the PubMed and Sciencedirect databases. Keywords used to search for articles such as quercetin, antidiabetic, blood glucose, and rats. Data were analyzed using R studio software version 4.3.3 using continuous data. Results: The articles used in this study in experimental studies amounted to 7 studies that are suitable for this meta-analysis. The results showed a significant difference in the effect of quercetin on reducing blood glucose levels in type 2 DM rats between control and intervention variables with a mean difference value (MD = -99.21 [-172.54; -25.87]). Conclusion: Administration of quercetin as an antidiabetic has an effect in reducing blood glucose levels in type 2 DM rats.